Strategy to Increase Farmers’ Income through Community-Based Organic Waste Management - Widjanarko Hendro; Sugiarto Bambang; Wahyurini Endah; Dyahjatmayanti Dhiani; Santosa Utomo Humam (SHS Web of Conferences)
This research was conducted to formulate, implement and evaluate strategies for increasing farmers’ income through processing organic waste into organic fertilizer. The approach used in this study is action research. The study was conducted on farmer groups in Wukirsari village, Bantul, Yogyakarta. This research involved farmer groups and the Wukirsari village government. Data was collected using focus group discussions, in-depth interviews, and questionnaires. The results of this research found that processing waste into organic fertilizer has been proven to reduce farmers’ operational costs and increase farmers’ income. The average reduction in fertilizer costs reached 32% and the average increase in farmer income was 28%. The study results show that the implementation of a strategy for collectively processing waste into organic fertilizer improves farmers’ welfare.